Perlindungan Hukum bagi Pekerja Platform terhadap Jaminan Sosial menurut Undang-Undang Ketenagakerjaan dan Badan Penyelenggara Jaminan Sosial - Manambe, Christofani; Azis , Rizka Amelia (IAI Nasional Laa Roiba Bogor, 2026)
The development of the digital economy has produced platform-based work models (the gig economy), raising challenges for the fulfilment of social security for freelance workers. This paper examines how legal protection for freelancers is regulated under labour legislation and social security policies (BPJS), and how the legal nature of the relationship between freelancers and companies affects the realization of rights to BPJS Employment and BPJS Health. The study employs a juridical-normative approach with a literature review of relevant laws, implementing regulations, and scholarly literature. The results indicate that, from a legal standpoint, there is a basis for freelancers’ access to social security, such as Law No.13/2003, Law No.24/2011, Government Regulation No.35/2021, and BPJS regulations, but freelancers are often categorized as Non-Wage Recipients. Consequently, registration and contribution payment in practice frequently depend on the initiative of the individual or the employer and on administrative enforcement. The determination of the substantive employment relationship (elements such as the task, remuneration, continuity, and supervision) is crucial for establishing employer obligations. It can be concluded that normative protection for freelancers under BPJS exists, but its implementation remains uneven; therefore, regulatory clarification specifically addressing freelancers, mechanisms for sharing contribution responsibilities, flexible contribution schemes by BPJS, and strengthened inspection and enforcement mechanisms are needed to close gaps in protection on the ground.